The Evaluatıon Of Facıal Profıle Changes In Indıvıduals Wıth Skeletal Class Iı Anomaly Treated Wıth Actıvator And Actıvator + Occıpıtal Headgear - Hakan Gögen; Şebnem Parlar (Galenos Yayinevi, 1989)
The aim of this study is to evaluate the changes occuring in facial profile in individuals treated with activator and activator + occipital headgear. Our study is based on two treatment groups namely activator and activator + occipital headgear and one control group which received no orthodontic treatment. In each group there were 18 individuals of which 108 lateral cephalometric films were obtained reftecting before and after treatment / control periods. In this research 18 measurements were made. According to the results, it is found out that there exists difference in treatment groups in terms of the movement of lips related to Steiner soft tissue line.